The role of literature in a personality’s worldview - G. Pirali, A. Ismakova,; A. Tanzharikova, B. Begmanova,; Oisylbay, A. (Opción, 2019)
The purpose of research consists in the judgment of the role of classical literature reading in the spiritual space of a person. To achieve this goal, we analyzed the features of the current state of reading, including overseas ones. As a result, Kazakhstan was one of the most reading countries in the world, home libraries were in vogue, and people gathered and discussed the same book. In conclusion, the process of socialization is endless, and the formation of a personality begins in childhood.